O17 Sexual health safeguarding advice line. (16th June 2022) - Tippetts, Darren; Ashby, Jane; Bennett, Amy; Doran, Jillian; McCarthy, Sarah; Nur, Marian
Abstract : Introduction of a single point of contact (SPOC) safeguarding (SG) advice line for Sexual Health (SH) staff working in a large urban and peri-urban service: 12 months data. Introduction Review indicated that timely access to SG advice could be delayed, and the quality of SG advice given was variable. We introduced a single point of contact (SPOC) safeguarding (SG) advice line for Sexual Health (SH), the aim of enabling direct access to real time, high quality safeguarding advice for all clinic staff. Methods: January 2021, all SG enquiries were managed via the SPOC, staffed by experienced SG leads during clinic opening times. SG advice calls were logged, recorded and analysed. Results: The SG SPOC received 400 calls in the first year, increasing from 42 in the first quarter, to 132 in the 4th quarter. Themes of calls received are shown in table 1. Advice calls were received from members of the MDT. Nurses 182 (46%), Doctors 121 (30%), psychology 41 (10%) and admin staff 34 (9%). 85% of calls were between 9:00 – 17:00; calls after 17:00 were found to involve more complex issues. Discussion: The SPOC was well used, and calls have increased. It has enabled staff access to standardised, expert SG advice in real-time. This has increased access to advice and prompted and supported safeguarding risk assessments, interventions and signposting of patients whilst they are present within our services. Themes of calls are used to tailor training for staff. Opportunistic teaching has improved general SG competence and supplemented formal supervision